'Epidemic neuromyasthenia' at the Hospital for Sick Children, Great Ormond Street, London. Issue 637 (November 1978) - Dillon, M. J.
Abstract : An outbreak of an illness with features in common with 'epidemic neuromyasthenia' affected the staff of the Hospital for Sick Children in London between August 1970 and January 1971. At least 145 cases were observed and the majority of these were nurses. Symptomatology was protean, clinical findings minimal and relapses frequent. Care was taken to minimize anxiety and fear in a vulnerable population, and laboratory investigations were purposefully limited in number for this reason. In general, laboratory findings, including virological investigations were negative. A high incidence of anti-complementary activity and the presence of ill defined aggregates in some acute sera on electron microscopy were interesting and possibly significant findings suggesting the presence of immune complexes. These findings, plus the ability of lymphocytes from some patients to proliferate in vitro, were thought to represent possible evidence of an infective process. Although no children were affected during the 1970 outbreak, it is interesting that seven children have recently been referred to the hospital with features compatible with 'epidemic neuromyasthenia'.